1999
DOI: 10.1046/j.1365-2362.1999.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinetics of human apolipoprotein A‐I variants in rabbits

Abstract: Genetic variants of apo A-I with a single amino acid substitution show abnormal kinetics, and the electric charge of a apo A-I variant could contribute to determining its kinetics in vivo in this xenologous model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The AIM half-life of 40 hours evaluated in the present study is twice that of homologous rabbit or human apoA-I observed in kinetic studies performed in rabbits. 26,28 Similarly, kinetic studies of dimeric AIM in humans clearly indicated an increased residence time in the circulation compared with monomeric AIM or wild-type apoA-I. 29 This finding was recently confirmed in a clinical investigation comparing AIM to the chemically similar apoA-I Paris variant.…”
Section: Discussionmentioning
confidence: 87%
“…The AIM half-life of 40 hours evaluated in the present study is twice that of homologous rabbit or human apoA-I observed in kinetic studies performed in rabbits. 26,28 Similarly, kinetic studies of dimeric AIM in humans clearly indicated an increased residence time in the circulation compared with monomeric AIM or wild-type apoA-I. 29 This finding was recently confirmed in a clinical investigation comparing AIM to the chemically similar apoA-I Paris variant.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, further investigation of their properties contributes to the beĴer understanding of their individual metabolism and physiological function (Davidson et al, 1995;Colvin & Parks, 1999). Such physiological role is a function of small size (Oram et al, 1981;Dory et al, 1986), high negative charge (Desrumaux et al, 1989;Dory et al, 1986;Sparks et al, 1995;Saku et al, 1999), high diffusion (Castro & Fielding, 1988), and low thermodynamic stability (Sparks et al, 1999) of the particles. The physico-chemical properties of macromolecules are commonly determined from the study of their displacement in solution by the effect of an external gradient of a potential caused by either electrical (electrophoresis) or gravitational (sedimentation) forces (Giddings, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Excess Na 125 I was removed by gel filtration using a PD-10 column (Amersham Pharmacia Biotech, Tokyo, Japan) and dialyzed against a solution of 0.85% NaCl. Human 125 I-apoA-I (specific activity: 2114 dpm/ng) was associated with unlabeled rabbit HDL overnight at 4°C and purified by ultracentrifugation before injection into the marginal auricular vein of Group 1 rabbits, as we described previously (25,38). Briefly, the mixture of human 125 I-apoA-I and rabbit HDL was adjusted to a density of 1.21 g/mL using solid KBr and ultracentrifuged using a TLA-100.3 rotor for 10 h at 541,000 × g and 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Human 125 I-apoA-I (specific activity: 604 dpm/ng) was associated with unlabeled rabbit HDL at 4°C overnight and purified by ultracentrifugation (25,38) before injection into the marginal auricular veins of Group 2 rabbits. Rabbit 125 I-apoA-I (specific activity: 613 dpm/ng) separated by the guanidine HCl method was reassociated with rabbit plasma for 30 min at 37°C, as described by Brousseau et al (39), and injected into Group 5 rabbits.…”
Section: Methodsmentioning
confidence: 99%